Time-Varying Spectral Modelling of the Solo Violin Tone - Soan, Oug Bee; Aug, Minni K. (Universiti Putra Malaysia Press, 2003)
The analysis of the spectrum of a single violin tone, to better understand how the various partial components contribute to the sound produced, is undertaken. The analysis involves determining which partials are present and how these partials evolve with respect to time. The short-time Fourier transform is used to implement a solution for the time varying spectra by slicing the sound into short segments called windows and analysing each segment sequentially. A digital signal processing software was used in both the analysis and resynthesis stages of this research. Parameters extracted through analysis are used for resynthesis purposes. Results indicate that spectrum changes over time contribute significantly to the timbre of the violin tone. Aslight shifting of the fundamental frequency was also observed in the sound spectrum of all the sub-sections of the waveform, although this shifting was most marked in the attack and release portions of the ADSR envelope. The results also showed that the intensity of the fundamental harmonic was weaker in the initial attack stage, only dominating when the timbre of the tone stabilised. Within the release portion, inharmonic overtones were shown to occur in the upper partials of the sound spectrum. Finally, the resynthesis process reduces the required hard disk capacity by about 93.8% compared with the sampled waveform, while at the same time producing an audible tone almost indistinguishable from the original.